Marketing the Count’s way: how Dracula’s myth can revive Romanian tourism - Candrea, Adina Nicoleta; Ispas, Ana; Untaru, Elena Nicoleta (My University, 2016)
Tourism destinations associated with the place myth phenomena often experience increased visitation and marketing opportunities. Considering the popularity of the Dracula myth worldwide, Romania has a great opportunity to improve its image as a unique destination on the international tourism market. Thus, the present study aims to analyze the exploitation of the Dracula myth in the Romanian tourism context, as well as the managerial and marketing implications of such an approach. It begins with an overview of the imaginary and historical links between Romania and the Dracula myth. Further on, it reviews the national initiatives to develop Dracula tourism, from both private and governmental perspectives. The paper concludes by highlighting the opportunities of developing Dracula tourism in Romania and embracing the Dracula myth as a unique competitive advantage of the country as a tourism destination.
Keywords: Dracula tourism; tourism destination